(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: To report a clinical case after direct trauma which caused elbow dislocation and radial head fracture to discuss the clinical features and treatment of this case. Result: After 3 months of surgery, the patient came to the clinic again with a happier expression because the movement had improved more than before, with the pronation / supination range reaching 90 degrees / 0 / 80 degrees. Conclusion: Radial head fracture is a type of fracture that affects pronation, supination of the forearm, and elbow flexion. Surgical treatment and postoperative care require the surgeon to understand the classification, indications and treatment techniques in order to restore the anatomy and function of the elbow joint.